2013
DOI: 10.1097/sap.0b013e31824e29a4
|View full text |Cite
|
Sign up to set email alerts
|

The “Chimeric” Trapezius Muscle and Fasciocutaneous Flap (Dorsal Scapular Artery Perforator Flap)

Abstract: This concomitant use of a muscle and fasciocutaneous perforator flap based on a single perforator, a so-called chimeric perforator flap, is a useful modification to trapezius musculocutaneous flap design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Numerous studies have reported on the use of pedicled LTMC flaps for reconstruction of various defects. [2][3][4][5][6][7][8][9] However, this type of flap is generally transferred to the recipient site through a subcutaneous tunnel, resulting in unavoidable waste of normal tissue and cosmetically unacceptable bulging of the tunnel region. We propose that raising an LTMC flap in a propeller fashion is a superior and reliable technique that can avoid these problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported on the use of pedicled LTMC flaps for reconstruction of various defects. [2][3][4][5][6][7][8][9] However, this type of flap is generally transferred to the recipient site through a subcutaneous tunnel, resulting in unavoidable waste of normal tissue and cosmetically unacceptable bulging of the tunnel region. We propose that raising an LTMC flap in a propeller fashion is a superior and reliable technique that can avoid these problems.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The pedicled LTMC flap has been widely used to reconstruct soft tissue defects in the head, 4,5 neck, 6,7 and back. 8,9 Generally, this flap is transferred to the recipient site through a subcutaneous tunnel, and a portion of the flap buried in the tunnel needs to be de-epithelialized. 10 Therefore, a considerable amount of normal skin is sacrificed if the flap is used to reconstruct a defect far from the donor site.…”
mentioning
confidence: 99%
“…Reconstruction of complex back defects, especially following spinal surgery, presents a variety of challenges for the reconstructive surgeon, and such cases may be additionally complicated by previous surgeries, planned instrumentation, and altered anatomy. Furthermore, patients undergoing spinal surgery and subsequent reconstruction are subject to a multitude of postoperative complications, including infection, wound‐dehiscence, seroma, hematoma, hardware exposure, and cerebrospinal fluid leak (Chieng et al, ; Rozen et al, ; Saint‐Cyr et al, ). However, it has been shown that adequate coverage of posterior trunk defects with robust muscle flaps both decreased postreconstructive complication rates, and provide strategies for the salvage of infected hardware (Cohen et al, ; Dumanian et al, ; Hultman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As observed in our patients, routine reconstructive options, such as paraspinous muscles flaps, may be unavailable secondary to scarring from previous spinal surgery. To create local flaps in this region, reconstructive surgeons have utilized specialized techniques such as perforator flaps and propeller flaps (Oh, Hallock, & Hong, ; Rozen, Fox, Leong, & Morsi, ). These previously described reconstructive options have been fasciocutaneous flaps, either advanced or rotated for coverage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation